THE INFLUENCE OF SOFT SKILLS AND HARD SKILLS ON THE PERFORMANCE - Machda Namora Aglaonema; Daris Zunaida; Eny Widayawati (Universitas Islam Malang, 2023)
The target of this study is to observe the impact soft skills & hard skills on employee performance. This study uses a quantitative method. The data source used is primary data, especially through distributing questionnaires. This study had a population of workers in the manufacturing department of PT. JFE Steel Galvanizing Indonesia. To take samples using saturated sampling a total of 95 respondents. This research provides results that the soft skills variable has an influence but is not significant on employee performance, given the fact that the sig level ( 0.299 > 0.05) and tcount < ttable (1.044 < 1.986). Then, the hard skills variable has a partial impact on employee performance, observed through the sign level (0.000 < 0.05) as well as tcount > ttable (16.422 > 1.986). Through simultaneous test results it can be seen that soft skills & Hard skills have a significant impact on employee performance, through the sign level (0.000 < 0.05) and Fcount > Ftable (186.578 > 3.097).